Time domain buffeting analysis of a large span cable-stayed bridge - Shuxian Hong (2010)
Large-span cable-stayed bridges are flexible structures susceptible to various types of wind-induced vibrations such as buffeting. In this study, a time domain buffeting analysis procedure is formulated and implemented by developing a toolbox based on ANSYS Parametric Design Language (APDL). To illustrate the potential of the toolbox, a real wind excited cable-stayed bridge built in China is taken as a case study. A comparison with results obtained including buffeting loads modeled by a quasisteady approach is discussed. The results also show good agreement with those from the frequency domain analysis.